2019
DOI: 10.3389/fncel.2019.00511
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress-Mediated Basolateral Amygdala GABAergic Neuron Injury Is Associated With Stress-Induced Mental Disorders in Rats

Abstract: The amygdala is an important center of fear learning and memory and plays a critical role in regulating stress disorders. Previous studies have shown that changes in the amygdala caused by stress are an important cause of mental disorders including anxiety, but the specific mechanism remains unclear. Therefore, the purpose of this study was to investigate whether mental disorders induced by stress are related to γ-aminobutyric acid (GABA)ergic neuron damage in the basolateral amygdala (BLA) and whether endopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
(53 reference statements)
2
13
0
Order By: Relevance
“…It could be because of the fact that FJB fluorescence staining is more sensitive than H&E staining. In agreement with the previous studies, our results provide morphological evidence that chronic stress can lead to degeneration and death of GABAergic neurons [15] and astrocytes [34], leading to the decrease of the amygdala volume and may be related to the degeneration and death of glutamatergic neurons in the BLA nucleus.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It could be because of the fact that FJB fluorescence staining is more sensitive than H&E staining. In agreement with the previous studies, our results provide morphological evidence that chronic stress can lead to degeneration and death of GABAergic neurons [15] and astrocytes [34], leading to the decrease of the amygdala volume and may be related to the degeneration and death of glutamatergic neurons in the BLA nucleus.…”
Section: Discussionsupporting
confidence: 93%
“…But, with increasing stress duration and intensity, p-eIF-2α activates the expression of transcription factor ATF4, further promoting the expression of CHOP, thereby leading to neuronal injury and death [39,40]. Previous studies have confirmed that ER stress plays an important role in neuronal injury and the pathogenesis of neurodegenerative diseases [15,18,19,41]. In order to confirm whether ER stress-associated PERK pathway plays a role in stress-induced degeneration and death of glutamatergic neurons, we used a specific inhibitor Sal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that stress could lead to anhedonia in animals [ 28 ] that has been associated with dysfunctions in the reward system, particularly in the dopamine system [ 29 ]. Stress also resulted in anxiety and depression disorders [ 30 ], and neuroimaging, pharmacological, and electrophysiological methods were employed by researchers in humans and animal models, providing support for the presence of dopamine dysfunctions [ 31 ]. Particularly, Tye and collaborators [ 32 ] indicated that stress-induced abnormal behaviors could be reversed by selective activation of the dopamine system.…”
Section: Discussionmentioning
confidence: 99%
“…More studies are required to understand how the mutant neuroligin3 induced UPR activation is related to ASD associated synaptic pathologies. PERK has also been linked to stress-induced anxiety, and reducing PERK was found to mitigate ER stress-induced GABAergic neuron damage in rat basolateral amygdala (Wang S. et al, 2019 ).…”
Section: Perk Signalingmentioning
confidence: 99%